1998
DOI: 10.1107/s0108768198007381
|View full text |Cite
|
Sign up to set email alerts
|

Arrays with Local Centers of Symmetry in Space Groups Pca21 and Pna21

Abstract: Of the several hundred structures in the Cambridge Structural Database [version 4.6 (1992), Cambridge Crystallographic Data Centre, 12 Union Road, Cambridge, England] having space groups Pca21 or Pna21 and more than one molecule in the asymmetric unit (Z > 4), approximately three-quarters contain local centers of symmetry. These local centers, which are not crystallographic centers, occur predominantly near x = 1\over8, y = 1\over4 in Pca21 or near x = 1\over8, y = 0 in Pna21; this also holds for the limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…24 and 25) show clearly that there is clustering in the distribution of pair centroids in Z 0 = 2 structures. There is some evidence for the annular distribution of pair centroids, like that observed for Z 0 = 1 structures; this is particularly evident from the apparent curvature of the occupied positions close to (x, y) = ( Again, comparison of these results with those of Marsh et al (1998) shows that the distributions are similar, but with a larger spread of centroid positions in this study resulting from the presence of local operators other than inversion centres.…”
Section: Figure 24supporting
confidence: 60%
See 3 more Smart Citations
“…24 and 25) show clearly that there is clustering in the distribution of pair centroids in Z 0 = 2 structures. There is some evidence for the annular distribution of pair centroids, like that observed for Z 0 = 1 structures; this is particularly evident from the apparent curvature of the occupied positions close to (x, y) = ( Again, comparison of these results with those of Marsh et al (1998) shows that the distributions are similar, but with a larger spread of centroid positions in this study resulting from the presence of local operators other than inversion centres.…”
Section: Figure 24supporting
confidence: 60%
“…These results make for an interesting comparison with the findings of Marsh et al (1998); the distributions are very similar in the xy projection, although here we observe many more structures where the two molecules are centred along a line of x = 1 4 , rather than being restricted to the point (x, y) = (0, 1 4 ). We suggest that this is because the independent molecules are related by operators other than centres of inversion.…”
Section: Figure 16mentioning
confidence: 61%
See 2 more Smart Citations
“…This is a noncrystallographic or local centre of symmetry, but it is not unusual to find such local centres. For example Marsh et al have found several structures, having space group Pca2 1 or Pna2 1 with more than one molecule in the asymmetric unit, containing local centres of symmetry [17], and Dalhus and Henrik report another example, also in Pca2 1 [18]. A situation similar to that observed for 1 was reported for 2-methylpyrazine [19] which crystallizes in the tetragonal space group I-4 with two independent molecules in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 52%